The Effectiveness Of Group Counseling With A Religiously Integrated Cognitive Behavioral Therapy Approach To Improve Students’ Self-Effucacy And Self-Regulation - Machmudah, Siti; Sutoyo, Anwar; Purwanto, Edy (Jurnal Bimbingan Konseling, 2022)
Low self-efficacy may affect students’ academic performance realized in the practice of procrastination. In the same way, low self-regulation can make students difficult in regulating emotion and behavior, which for sure will affect their performance in learning process. Here, the students of Public Islamic Junior High School or MTs Negeri 1 Kudus were found to have low self-efficacy and self-regulation. Thus, the present student strived for examining the effectiveness of group counseling with religiously integrated cognitive behavioral therapy which focuses on Islamic beliefs, namely using shirah nabawiyah technique to improve students’ self-efficacy and self-regulation. As many as 18 students involved as the subjects of this study were grouped into two and researched using randomized pretest posttest group design. The findings have proved that the group counseling with religiously integrated cognitive behavioral therapy approach is effective to improve students’ self-efficacy and self-regulation. Further discussion of the implication and limitations can be found in the discussion chapter.